PATOPHYSIOLOGY AND LATEST TREATMENT OPTIONS OF VASCULITIS: A LITERATURE REVIEW - Suryantarini, Ni Wayan Puspa Wijaya; Satriawan, Wira (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Inflammation is a body defense process against various potentially damaging causes. Excessive inflammation in the vascular can cause an autoimmune process in vasculitis disease. Vasculitis can cause damage to the tissues and organs that are vascularized. So far, the heterogeneous pathophysiology and clinical manifestations of the disease have been well understood. Although therapy with glucocorticoids is effective for disease remission, complications that often occur earlier in patients can fail the therapy. Therefore, a more effective method for accurate diagnosis is needed as a patient management approach. A more detailed and interrelated understanding of the disease will further encourage the improvement of the quality of the medical procedures so that it is expected to improve the patient’s prognosis. This literature review aimed to explain detail started from the prevalence of vasculitis cases, followed by the underlying risk factors and the development of effective diagnostic and management flows to date. The method of this literature review was searching for articles from various databases in PubMed, Google Scholar, and the Google search engine. Based on various literature obtained, each classification of vasculitis has unique characteristics including the type of inflammation that occurs and the onset of the disease that differs for each age group. The diagnostic flow still starts from anamnesis to the use of imaging and laboratory examinations and the application of criteria for a definitive diagnosis. Further management is differentiated based on the type of vasculitis, treatment phase, and response to therapy. Further studies are needed, especially in determining the reference values ​​of laboratory examinations used for diagnosis, determining the dose of therapy, and efforts to treat complications that occur. Vasculitis remains a heterogeneous autoimmune disease that requires further attention in efforts to establish a diagnosis and apply the most appropriate management to the patient’s condition.